Translation and style - Boase-Beier, Jean (Translation theories explored, 2021)
"Style plays a major role in the translation of literary, as well as non-literary texts, and Translation and Style offers an updated survey of this highly interdisciplinary area of translation studies. Jean Boase-Beier examines a variety of disciplines and theoretical approaches including stylistics, literary criticism, and narratology to investigate how we translate style. This revised and expanded edition of the 2006 book Stylistic Approaches to Translation offers new and accessible explanations on recent developments in the field, notably in the areas of relevance theory and cognitive stylistics. With many authentic examples to show how style affects translation, this book is an invaluable resource for both students and scholars working in translation studies and comparative literature."--Provided by publisher.